Improve product quality and production process with integration of six sigma and quality management system ISO 9001: A case study of bakery shop in France - Norfaizah, Yusof; Lee, Khai Loon (Penerbit Universiti Malaysia Pahang, 2022)
This study highlights macarons product research conducted in a bakery shop in France. It is aims to optimize the quality of the macarons products via the integration of Six Sigma and Quality Management System, ISO 9001. To achieve the objective, the study first identifies the primary root cause of product defects. Besides, an alternative standard operating procedure is incorporated with the recommended improvements. The DMAIC approach is emphasized by the Six Sigma approach, which is Define-Measure-Analyze-Improve-Control. According to the data, the cost of poor quality for a month is 34,511.40 Euro. Cracked macarons (53.70%), hollow macarons (16.30%), and no feet macarons (16.10%) are three major critical defects. The macarons product has a Sigma level of 2.50. The parameters proposed in this study are low-level mixing at 80 rpm, 12 minutes of baking time, and 203°c oven temperature to improve the quality of macarons product using the Design of Experiment (DOE) of the Taguchi Method. When the major elements are controlled inside the processes, the company's chances of producing a high-quality product increase significantly. As a result of adopting Six Sigma with Quality Management System ISO 9001 into the macaron manufacturing process, defects costs and rate is expected to be lower.